2019
DOI: 10.24288/jttr.573851
|View full text |Cite
|
Sign up to set email alerts
|

The effects of psychological capital on employees’ organizational identification in hotels

Abstract: The purpose of this study was to examine the effects of dimensions of psychological capital on employees' organizational identification in hotels. Through conducting a face-to-face interview, data were collected from a sample of 485 full-time employees working in 5-star hotels in Turkey and were analysed with statistical program. The correlation analysis was used to investigate the relationship between independent variables and dependent variable and the regression analysis was used to determine the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Focusing on revealing and developing the present abilities and characteristics of the employees working in the kitchen department by hotel management (Seligman & Csikszentmihalyi, 2000) will contribute to increasing the psychological capital of employees. In addition, being aware of the fact that the employees' personal negativities, such as weakness, incompetence, and defects, have a positive equivalence and can be developed (Demir & Şen Demir, 2019); thus, acting in line with this awareness will contribute to increasing the psychological capital of employees. What is more, it has been determined that employees in the front office department show higher emotional labor behaviour and the level of displaying emotional labor behaviour decreases as the working time in the sector increases.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Focusing on revealing and developing the present abilities and characteristics of the employees working in the kitchen department by hotel management (Seligman & Csikszentmihalyi, 2000) will contribute to increasing the psychological capital of employees. In addition, being aware of the fact that the employees' personal negativities, such as weakness, incompetence, and defects, have a positive equivalence and can be developed (Demir & Şen Demir, 2019); thus, acting in line with this awareness will contribute to increasing the psychological capital of employees. What is more, it has been determined that employees in the front office department show higher emotional labor behaviour and the level of displaying emotional labor behaviour decreases as the working time in the sector increases.…”
Section: Discussionmentioning
confidence: 99%
“…In the investigations performed by Kumlu & Güçlü Nergiz (2018) and Kodaş (2018), a positive and strong relationship was found between psychological capital and organizational citizenship behaviour. In the studies conducted on hotel enterprises, Demir & Şen Demir (2019) found a positive relationship between psychological capital and organizational identification. Suna & Okun (2019) determined a positive relationship between the psychological capital and personal innovativeness.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations